전당뇨병 성인에서 나트륨 섭취와 복부비만과의 상관관계 - 임소영(So Young Lim); 양수진(Soo Jin Yang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
The objective of this study was to assess the relationship between dietary sodium intake and prevalence of abdominal obesity in Korean adults. We used data from the Korea National Health and Nutrition Examination Survey V-1 and analyzed data on 4,475 Koreans (${≥}30$ years old). Subjects were divided into three groups according to fasting plasma glucose (FPG): 1) normal (FPG <100 mg/dL), 2) pre-diabetes ($100mg/dL{≤}FPG{≤}125mg/dL$), and 3) diabetes (FPG ${≥}126mg/dL$ or subjects diagnosed with diabetes). The subjects in each category were stratified by dietary sodium intake as well as index of abdominal obesity. We found that dietary sodium intake was positively correlated with waist circumference (WC) (P=0.002) and was particularly high in the pre-diabetes group. In multiple logistic regression analysis, the normal and diabetes groups showed no association between dietary sodium intake and WC, whereas the pre-diabetes group with a high sodium intake exhibited a significant association (odds ratio (OR)=1.479, P=0.029) between dietary sodium intake and WC. Further, the OR for abdominal obesity in the high sodium intake group with pre-diabetes was 1.590 after adjusting for age and sex (P=0.012). In addition, the ORs for the prevalence of abdominal obesity with fasting glucose, fasting insulin, and homeostasis model assessment of insulin resistance were significantly higher in the pre-diabetes group with high sodium intake compared with low sodium intake. Moreover, these associations were significant even after adjusting for confounding variables (model 2: age and sex; model 3: age, sex, and total energy intake). Our results suggest a strong association between sodium intake and abdominal obesity in pre-diabetes Korean adults. 본 연구는 국민건강영양조사 2010년 자료를 이용하여 우리나라 만 30세 이상 성인을 대상으로 공복혈당에 따라 정상군, 전당뇨병군, 당뇨병군으로 나누어 각 군에서 나트륨 섭취량과 복부비만과의 상관성을 분석하고자 하였다. 분석 결과, 전당뇨병군에서 나트륨 섭취와 복부비만 관련 지표인 허리둘레가 유의적인 양의 상관관계를 보였으며, 특히 전당뇨병 고나트륨군의 경우 당뇨병 관련 임상지표인 공복혈당, 공복인슐린, HOMA-IR 수치가 높아질수록 복부비만 발병위험 또한 유의적으로 증가하였다. 본 연구는 당뇨병과 여러 관련 합병증으로 이행될 위험이 높은 전당뇨병 대상자에서 나트륨 섭취와 복부비만 간 상관성을 밝혔다는 점에 의의가 있다. 우리나라 전당뇨병 성인의 경우 나트륨 섭취 수준이 높다고 분석되었으므로 추후 연구에서는 전당뇨병 대상자를 위한 지속적인 나트륨 섭취량 모니터링과 함께 나트륨 섭취가 복부비만과 당뇨병에 미치는 인과관계와 그 기전을 밝힐 수 있는 연구가 필요하며, 이를 통해 당뇨병과 여러 관련 합병증의 예방 및 관리를 위한 적절한 식사지침과 효과적인 영양교육을 제시할 수 있을 것으로 사료된다.